The first true Mordellidae (Coleoptera: Tenebrionoidea) from lower Cenomanian amber of Myanmar. (January 2019) - Bao, Tong; Walczyńska, Katarzyna S.; Moody, Samantha; Wang, Bo; Rust, Jes
Abstract: Primaevomordellida burmitina gen. et sp. nov. (Coleoptera: Mordellidae) is described on the base of two well-preserved specimens from Cenomanian Burmese amber. Due to the general body plan and the preservation of elongated pygidium, it is apparently the first true pintail beetle (subfamily Mordellinae). The simple hind leg structures placed the new species into the basal tribe Raynoldsiellini; however, the comparative morphology of the new species shows advanced characters similar to tribes Mordellini and Mordellistenini. The angiosperm plant records in Burmese amber forests were reviewed and the mordellids-angiosperm interactions are discussed.